Multimodal Imaging of Dynamic Functional Connectivity - Tagliazucchi, Enzo; Laufs, Helmut (Frontiers in Neurology, 2015)
The study of large-scale functional interactions in the human brain with fMRI extends almost to the first applications of this technology. Due to historical reasons and preconceptions about the limitations of this brain imaging method, most studies have focused on assessing connectivity over extended periods of time. It is now clear that fMRI can resolve the temporal dynamics of functional connectivity, like other faster imaging techniques such as EEG and MEG (albeit on a different temporal scale). However, the indirect nature of fMRI measurements can hinder the interpretability of the results. After briefly summarizing recent advances in the field, we discuss how the simultaneous combination of fMRI with electrophysiological activity measurements can contribute to a better understanding of dynamic functional connectivity in humans both during rest and task, wakefulness and other brain states.